Scale ontogeny in the cardinalfish family Apogonidae - Gon, Ofer (Zootaxa, 2016)
Following the discovery of spinoid scales in species of the cardinalfish genus Siphamia, a survey of 20 apogonid genera, using scanning electron microscopy, found that scale ontogeny in the Apogonidae usually proceeds along three phases, cycloid, spinoid and transforming ctenoid, that develop in that order. The transforming ctenoid scales of the Pempheridae, considered a sister group of the Apgogonidae by some authors, follow the same ontogenetic pattern. Transforming ctenoid scales are the ancestral scale type in the Apogonidae, making their spinoid and cycloid scales a secondary loss or reversal. Though sharing the transforming ctenoid scale type with the apogonids, the ontogeny of this scale type in several scorpionfishes (Scorpaenidae) does not have a spinoid phase. Recent molecular studies indicate that gobiids are related to apogonids, but the goby species examined in this study have peripheral ctenoid scales that lacked a spinoid phase in their ontogeny. The observations made in this study suggest that the peripheral ctenoid scale, the whole ctenoid scale and the crenate scale found in percomorph fishes were derived from a transforming ctenoid scale. Scale morphology and ontogeny could provide useful characters for resolving relationships between percomorph families.